2018
DOI: 10.3390/s18124433
|View full text |Cite
|
Sign up to set email alerts
|

A Path Loss and Shadowing Model for Multilink Vehicle-to-Vehicle Channels in Urban Intersections

Abstract: The non line-of-sight (NLOS) scenario in urban intersections is critical in terms of traffic safety—a scenario where Vehicle-to-Vehicle (V2V) communication really can make a difference by enabling communication and detection of vehicles around building corners. A few NLOS V2V channel models exist in the literature but they all have some form of limitation, and therefore further research is need. In this paper, we present an alternative NLOS path loss model based on analysis from measured V2V communication chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 29 publications
0
22
2
Order By: Relevance
“…Since radio receivers require a certain minimum power (sensitivity) to be able to successfully decode information, path loss prediction is essential in mobile communications network design and planning such as link budget, coverage analysis, and locating base station. Many existing path loss models [1][2][3][4][5][6][7][8][9][10][11][12][13][14] adopt a linear log-distance model, which is empirically derived by assuming a linear proportionality between the path length and the path loss, and by determining a proportional factor through the adequate linear regression analysis of the measured data. The linear log-distance model is simple and tractable, but it does not guarantee accurate path loss prediction performance for all radio propagation environments.…”
Section: Introductionmentioning
confidence: 99%
“…Since radio receivers require a certain minimum power (sensitivity) to be able to successfully decode information, path loss prediction is essential in mobile communications network design and planning such as link budget, coverage analysis, and locating base station. Many existing path loss models [1][2][3][4][5][6][7][8][9][10][11][12][13][14] adopt a linear log-distance model, which is empirically derived by assuming a linear proportionality between the path length and the path loss, and by determining a proportional factor through the adequate linear regression analysis of the measured data. The linear log-distance model is simple and tractable, but it does not guarantee accurate path loss prediction performance for all radio propagation environments.…”
Section: Introductionmentioning
confidence: 99%
“…The next generation of autonomous vehicles that will assist or completely replace the driving system in vehicles will be implemented on top of this technology. As a result, there has been extensive research on ADAS systems in recent years, the variety of on-board sensors (e.g., radars, cameras, and LiDARs) are used to reduce the number of traffic accidents and deaths [ 5 ]. Although ADAS applications are still in the early stages, they will transform the driving experience and simultaneously provide road safety.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main disadvantages of these models is that they must be employed in environments similar to those used in their estimation, requiring strong modifications for their use in other environments, and in many cases, they are simply ineffective outside of these scenarios [ 25 ]. Some empirical studies regarding sub 6 GHz vehicular propagation channels can be found in the literature like [ 5 , 26 , 27 ]. Non-geometric stochastic models (NGSCM) are used to predict the values regarding the modeled system, taking into account the occurrence of random elements within the system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is usually necessary to develop new empirical models for each new communication system. Empirical models and measurements are used to study the propagation losses between moving cars in the urban environment [7,8]. Similar research has been conducted for the vehicle-to-infrastructure (V2I) scenario [9].…”
Section: Introductionmentioning
confidence: 99%